PENGARUH INFLASI DAN BI 7-DAY REVERSE REPO RATE TERHADAP ROA BANK UMUM DI INDONESIA TAHUN 2019-2022 - Pratama, Arizal Putra; Roy Tutupoho, Ridwan; Kadunci; Nilla Chandra, Yanita Ella; Akbar, Djuni (Jurnal Administrasi Profesional, 2024)
The uncertain global economy during the Covid-19 pandemic during 2020-2022 means that Indonesia must be able to adapt to these conditions. The government, through the Financial Services Authority (OJK), issued a policy that can provide stimulus to the economy in Indonesia, especially the banking industry, so that society is not burdened further in the limited situation at that time. Restrictions on community activities aimed at suppressing the spread of the corona virus have become a challenge for banks in Indonesia to carry out their functions as business entities that collect and distribute public funds. The research examines the influence of the BI 7-day Reverse Repo Rate (BI7DRRR) and inflation on Return on Assets (ROA) of commercial banks in Indonesia during the 2019-2022 period. This year's period shows the conditions in 2019, namely before the Covid-19 pandemic, during the Covid-19 pandemic, namely 2020-2021 and after the Covid-19 pandemic, namely 2022. The method used in this research is quantitative using secondary data from the OJK, using multiple linear analysis techniques.